Changing Environments and Management IR Practices. Implications for US Trade Unions - Reshef, Yonatan (Relations industrielles / Industrial Relations, 1988)
Since the first oil shock of 1973, in the U.S., significant changes have shaken long-standing industrial relations patterns in the union manufacturing sector. This paper concentrates on the challenges posed to manufacturing unions by changing environments and management industrial relations practices.